2022
DOI: 10.1007/s00420-022-01862-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term sick leave for back pain, exposure to physical workload and psychosocial factors at work, and risk of disability and early-age retirement among aged Swedish workers

Abstract: Purpose To assess the risk of disability and early-age retirement associated with previous long-term sickness absence for back pain (back-pain SA), exposure to high physical workload, low job control, high demands and high strain, and to evaluate effect modification by work factors on the relationship between back-pain SA and premature retirement. Methods All employed Swedish residents born 1946–1955 (n = 835,956) were followed up from 2010 to 2016 for dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 61 publications
2
13
1
Order By: Relevance
“…In line with previous studies that reported gender-specific outcomes among older workers [ 14 , 18 , 20 ], the results from the present study indicate that biomechanical and psychosocial work exposures are associated with age of withdrawal from paid employment among both men and women and that some gender differences in the associations exist.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In line with previous studies that reported gender-specific outcomes among older workers [ 14 , 18 , 20 ], the results from the present study indicate that biomechanical and psychosocial work exposures are associated with age of withdrawal from paid employment among both men and women and that some gender differences in the associations exist.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, knowledge of how work exposures are associated with early withdrawal from work among older workers is vital to extend working life successfully. Previous studies have examined biomechanical and psychosocial work exposures among older workers with respect to early retirement [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ], disability retirement [ 8 , 14 , 16 , 18 , 19 , 20 ], long-term sickness absence [ 16 , 19 ] and unemployment [ 8 , 16 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations